Architecture, state modernism and cultural nationalism in the apartheid capital - Judin, Hilton (Milton Park, Abingdon ; New York : Routledge, 2021)
"This book is the first comprehensive investigation of the architecture of the apartheid state in the period of economic growth, social engineering and political repression from 1957 to 1966 when buildings took on ideological and nationalistic roles that were never remote from the increasingly predominant administrative, legislative and policing mechanisms of the regime. The book examines in detail how this process reflected the usurpation of regionalism and the International Style and contributes to the wider discourse on international post-war modernism in architecture. A group of key state building projects in Pretoria that came to embody the ambitions of the apartheid regime for industrialisation and progress serve as detailed case studies. Architects drew heavily on the idea of modernity and the vernacular, as the relationship between the agricultural rural and industrialised urban was transforming in the capital city of Pretoria. Grappling with architectural form in an age of enormous technological change had challenged architects' intent on giving expression to the idea of a shared modernity as much as an embrace of 'western civilization.' There was an understanding by the governing Nationalist Party of the symbolic resonance of highly visible buildings in the apartheid capital. Yet these buildings were being erected to consolidate a white presence in Africa just as black South Africans were being forcibly removed from the city, and the built environment was being stripped of contested traditional and everyday cultural traces of the entire black population. This book will appeal to students and scholars in architectural history as well as those with an interest in postcolonial studies, political science and social anthropology"--
Introduction : "South Africa builds ..." -- Apartheid ideology and architectural form : state building in Pretoria -- Atomic Research Centre -- Volkseie : Afrikaners and the University of Pretoria -- Emerging traditions : the vernacular in "separate development" -- Norman Eaton's glass cabinet : Wachthuis -- Hubris : isolated edifices, state apparatuses and a depleted vision -- Conclusion : architecture for ourselves.
OCLC-licensed vendor bibliographic record.
Keywords: Apartheid and architecture -- South Africa -- Pretoria; Architecture and state -- South Africa -- Pretoria; Modern movement (Architecture) -- South Africa -- Pretoria; Pretoria (South Africa) -- Buildings, structures, etc; ARCHITECTURE / Criticism; ARCHITECTURE / Study & Teaching; ARCHITECTURE / History